Model Of Innovative Management For Islamic Educational Organizations At Madrasah Diniyah Takmiliyah Awaliyah In Padakembang District, Tasikmalaya Regency - Saepulah AM; Mudofir Mudofir; Imam Makruf (International Journal of Social Sciences, 2026)
This article discusses organizational management innovation in Islamic educational institutions, specifically Madrasah Diniyah Takmiliyah Awaliyah (MDTA) in Padakembang District, Tasikmalaya Regency, Indonesia. The study was motivated by the need to improve the quality of management in non-formal Islamic educational institutions, which continue to face challenges related to managerial professionalism, limited resources, and adaptation to technological developments and evolving societal demands. The research aims to identify, analyze, and formulate the forms of Islamic educational management innovation implemented in MDTA institutions within the region. This study employed a descriptive qualitative approach plus information on Literature Review. Data were collected through observations, in-depth interviews, and documentation. The research participants included MDTA principals, teachers, institutional administrators, and educational stakeholders at the district level. Data were analyzed using an interactive process consisting of data reduction, data display, and conclusion drawing. The findings reveal that organizational management innovation in MDTA encompasses six major dimensions: (1) collaborative and visionary leadership innovation, (2) contextual and adaptive curriculum development, (3) continuous human resource capacity building through professional training, (4) administrative and instructional digitalization, (5) transparent and accountable financial management systems, and (6) institutional branding development to enhance competitiveness and public trust. Based on these six dimensions, this study proposes the Integrated Islamic Education Management Innovation Model (MIPI) as its principal novelty. The model integrates all dimensions of management innovation into a holistic, systemic, and sustainable management framework capable of improving the effectiveness, efficiency, and quality of Islamic educational services in MDTA institutions. The MIPI Model is expected to serve as an alternative framework for developing non-formal Islamic educational management in the era of digital transformation and increasing educational competition. Keywords: management innovation, Islamic education, Madrasah Diniyah Takmiliyah Awaliyah (MDTA), MIPI Model, Tasikmalaya.